Host-associated helminth diversity and microbiome composition contribute to anti-pathogen defences in tropical frogs impacted by forest fragmentation - Neely, Wesley J.; Souza, Kassia M.C. [UNESP]; Martins, Renato A.; Marshall, Vanessa M.; Buttimer, Shannon M.; de Assis, Ananda Brito [UNESP]; Medina, Daniel; Whetstone, Ross D.; Lyra, Mariana L. [UNESP]; Ribeiro, José Wagner [UNESP]; Greenspan, Sasha E.; Haddad, Célio F.B. [UNESP]; et al. (The Royal Society, 2024)
Habitat fragmentation can negatively impact wildlife populations by simplification of ecological interactions, but little is known about how these impacts extend to host-associated symbiotic communities. The symbiotic communities of amphibians play important roles in anti-pathogen defences, particularly against the amphibian chytrid fungus Batrachochytrium dendrobatidis (Bd). In this study, we analyse the role of macroparasitic helminth communities in concert with microbial communities in defending the host against Bd infection within the context of forest fragmentation. We found that skin microbial and helminth communities are disrupted at fragmented habitats, while gut microbiomes appear more resilient to environmental change. We also detected potential protective roles of helminth diversity and anti-pathogen microbial function in limiting Bd infection. Microbial network analysis revealed strong patterns of structure in both skin and gut communities, with helminths playing central roles in these networks. We reveal consistent roles of microbial and helminth diversity in driving host–pathogen interactions and the potential implications of fragmentation on host fitness.
Keywords: Boana faber; Brazil; co-infection; co-occurrence network analysis; deforestation; nematode